Lectotypification of the Linnaean name Acanthus spinosus (Acanthaceae) - Iamonico, Duilio; Peruzzi, Lorenzo (Phytotaxa, 2012)
The genus Acanthus Linnaeus (1753: 639) (Acanthaceae) is composed of 20 species distributed in Africa, southern Europe, southern Asia, and Australasia (McDade et al. 2005). Linnaeus (1753, 1756) published 5 names under Acanthus [A. dioscoridis Linnaeus (1756: 23), A. ilicifolius Linnaeus (1753: 639), A. maderaspatensis Linnaeus (1753: 639), A. mollis Linnaeus (1753: 639), A. spinosus Linnaeus (1753: 639)] of which two are currently referred to other genera (Jarvis 2007): A. ilicifolius L. is now accepted under Dilivaria Jussieu (1789: 103) as D. ilicifolia (L.) Jussieu (1789: 103), A. maderaspatensis L. under Blepharis Jussieu (1789: 103) as B. maderaspatensis (L.) Roth (1821: 320). One of these names, concerning the European flora, appears to be yet untypified, and it is therefore investigated here. Acanthus spinosus is known in mediterranean and south-eastern Europe (Italy, Croatia, Albania, Bulgaria, Crete, East Aegean islands, Greece), the Asiatic Turkey as well as in Algeria, and is currently accepted at specific rank (e.g., Marhold 2011).